Systematic Review and Meta-Analysis of the Efficacy and Safety Profile of Belimumab in Combination with Standard Therapy for Adults with Systemic Lupus Erythematosus - Mochamad Rangga Alif Dharmawan; Maftuchah Rochmanti; Awalia; Citrawati Dyah Kencono Wungu (Current Internal Medicine Research and Practice Surabaya Journal)
Introduction: Systemic lupus erythematosus (SLE) is a multi-system autoimmune disorder marked by pathogenic autoantibodies, resulting in considerable morbidity and mortality. Despite existing diverse treatment regimens, the need for more effective therapies persists. Recent advancements include monoclonal antibodies, such as belimumab, which can inhibit receptors tied to SLE’s pathogenesis. This meta-analysis aimed to evaluate the efficacy and safety of combining belimumab and standard therapy compared to placebo in SLE patients, utilizing as many indicators as possible to comprehensively assess the former's potential.